2022
DOI: 10.3390/app12042227
|View full text |Cite
|
Sign up to set email alerts
|

Applicability Study on Modified Argillaceous Slate as Subgrade Filling for High-Speed Railway

Abstract: Modifying weathered argillaceous slate (WAS) to fill the subgrades of high-speed railways not only leads to obvious environmental benefits but also significantly saves natural resources. Previous studies have used several additives together with cement/quicklime. Using cement/quicklime as an additive would also improve the strength of weathered soft rock. Therefore, cement/quicklime can be used effectively as a sustainable solution. To illustrate the feasibility of cement/quicklime in WAS improvement, the mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, all these polymer particles need to be hydrophilically modified, mainly due to the hydrophobic groups on the surface of the polymer particles, which have a lower interfacial adhesion force and lower co-crosslinking level. When applied to water-based mixed systems, this can cause a decrease in the stability, strength, toughness, and other physical properties of the mixed system [ 12 , 13 , 14 , 15 ]. Cheng et al [ 16 ], He et al [ 17 ], and Zhong et al [ 18 ] found that unmodified rubber powder cannot be dispersed when soaked in water, and when added to cement-based composite materials, its compressive strength is low, which can easily lead to a poor stability of the cement paste and the deterioration of its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, all these polymer particles need to be hydrophilically modified, mainly due to the hydrophobic groups on the surface of the polymer particles, which have a lower interfacial adhesion force and lower co-crosslinking level. When applied to water-based mixed systems, this can cause a decrease in the stability, strength, toughness, and other physical properties of the mixed system [ 12 , 13 , 14 , 15 ]. Cheng et al [ 16 ], He et al [ 17 ], and Zhong et al [ 18 ] found that unmodified rubber powder cannot be dispersed when soaked in water, and when added to cement-based composite materials, its compressive strength is low, which can easily lead to a poor stability of the cement paste and the deterioration of its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The unconfined compressive stress–strain curve can be obtained through the unconfined compressive strength test; the triaxial compression stress–strain curve can be obtained from the triaxial compression test, which generally has three stages: linear elasticity, yield, and ductile flow. Scholars have added soil conditioners to improve soil strength in their research on soil improvement experiments, including poly-Lys [ 65 ], foaming agents [ 66 , 67 ], reactive magnesium oxide [ 68 ], bentonite [ 69 , 70 ], cement [ 71 , 72 , 73 ], fiber [ 74 , 75 ], polyacrylamide [ 76 , 77 ], and quicklime [ 78 , 79 , 80 ]. The improvement effects using different contents of modifiers have been discussed, and the overall strength has improved; however, the production of soil modifiers such as cement and lime causes great pollution to the environment.…”
Section: Introductionmentioning
confidence: 99%